Fuzzy model to assess factors affecting productivity in pyme (Publicaciones en Ciencias y Tecnología, 2010)
In Venezuela, small- and medium sized companies PYME contribute considerably to economic activity and are a great employment generator. This article state a fuzzy model development which permit to evaluate the production factors that affect productivity, in order to estimate and minimize their impact and, in this way the company dosen‘t loose the use or resource level. The importance of this development lies in the use of fuzzy logic to evaluate the effect of factors like production and client satisfaction in PYME‘s productivity.
Keywords: Fuzzy Inference; Fuzzy Logic; PYME; Productivity